"Christianity is for rubes; Buddhism is for actors": U.S. media representations of Buddhism in the wake of the Tiger Woods' scandal - Scott A. Mitchell (Journal of Global Buddhism, 2015)
Critical analysis of U.S. media representations of Buddhists and Buddhism can reveal American attitudes toward this minority religion as well as how Buddhism is being spread in Western, non-Buddhist cultures. This paper examines such representations in the wake of revelations of Tiger Woods' sexual scandal, a time when Buddhism was much in the news. I argue that Buddhism was here deployed in the service of a pre-existing narrative of conflict between conservatives and liberals and, by making appeals to secular scholars to define Buddhism, Buddhist voices were obscured or ignored. Finally, despite having their own media outlets, U.S. Buddhists were unable to effectively counter such representations either by perpetuating pre-existing media narratives or by ignoring them altogether.